A Developmental Evolutionary Framework for Psychology. Issue 2 (June 2013) - Lickliter, Robert; Honeycutt, Hunter
Evolutionary psychology (EP) was founded on the metatheoretical assumptions of the modern (or neo-Darwinian) synthesis of evolutionary biology, which dichotomize internal from external sources of causation. By prioritizing the former, EP has promoted a preformationist view of individual development, which effectively divorces developmental from evolutionary analysis. The authors argue that these assumptions about development are in need of revision in light of recent advances in genomics, epigenetics, and developmental science. The authors outline a developmental evolutionary framework for psychology, a relational metatheory that integrates the study of developmental and evolutionary mechanisms within one explanatory framework. They argue that knowledge of the dynamics of developmental processes are necessary to illuminate mechanisms of evolutionary change and that the psychological sciences, particularly comparative and developmental psychology, are ideally positioned to contribute to this endeavor.